Activity-based reporter assays for the screening of abused substances in biological matrices. (7th February 2019) - Cannaert, Annelies; Vandeputte, Marthe; Wille, Sarah M. R.; Stove, Christophe P.
Abstract: The (ab)use of designer drugs and steroid hormones has gained popularity due to the lower chance of getting caught, as routine drug or doping tests may miss these (novel) compounds. Current analytical approaches mostly make use of targeted, structure-based techniques, such as immunoassays or mass spectrometry (MS)-based methods. However, these approaches have limitations, including a lack of cross-reactivity and the need for prior knowledge of molecular identity. This has initiated considerable interest in the so-called "untargeted" screening strategies to detect these compounds. The use of "untargeted" MS-based screening methods (e.g. gas chromatography MS and especially high-resolution MS) has gained considerable interest to detect and identify novel compounds. However, due to their expensive and time-consuming character, very sophisticated analytical methods are not ideal as a first-line screening method and are not routinely implemented in most laboratories. Given the above, it is clear that there lies potential in novel "untargeted" screening approaches, which are less expensive, more high-throughput-amenable and more routinely applicable. Activity-based assays, capable of monitoring the biological activity of an abused substance in a biological matrix, have been proposed as an alternative. These biological assays do not require knowledge about a compound's structure and could be used as a first-line screening tool to identify potentially positive samples. In this review, we focus on activity-based reporter bioassays for the detection of steroids and drugs of abuse in biological matrices. As for drugs of abuse, only bioassays for detecting cannabinoid or opioid activity in biological matrices are available, only (synthetic) cannabinoid receptor agonists and opioids are discussed.